PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MENYIMAK SISWA KELAS III SD XAVERIUS 1 PALEMBANG - Julia Aritonang (Universitas Katolik Musi Charitas, 2019)
This study aims to find out how (1) the needs analysis of Student Worksheets is listening for third grade students of Xaverius 1 Palembang Elementary School (2) design Worksheet Student Listening for third grade students of Xaverius 1 Palembang Elementary School (3) validation of Student Worksheet for Grade III students at SD Xaverius 1 Palembang. This research is a Research and Development (R & D) study that adapted the research procedures for the development of Borg and Gall. This study has a research limitation, namely up to the expert validation stage. This research was carried out with stages namely needs analysis, design of Student Worksheets, and expert validation. Subjects in the study were third grade homeroom teacher SD Xaverius 1 Palembang with interview data collection techniques. The results of the research and discussion are summarized as follows. First, the development of Student Worksheets listening to grade III SD Xaverius 1 students is needed. This is reinforced by the results of the needs analysis. Secondly, the design of the listening Worksheet for Students developed is in the form of a short answer problem. Third, the results of validation by six validators indicate that the development of Student Worksheets listening to third grade students of SD Xaverius 1 Palembang can be used with a slight revision.